Pengaruh Social Media Marketing, Kualitas Produk dan Lokasi Terhadap Keputusan Pembelian di Gerai Adila - Wijaya, Hansen; Yossinomita Yossinomita; Devitra, Joni (Prosiding Seminar Nasional Ilmu Teknik, 2025)
With the rapid growth of Jambi City's tourism sector, the demand for souvenir products as a representation of local culture has increased. However, this potential has resulted in fierce competition among businesses. To generate new customers, businesses require effective digital and physical marketing strategies. The purpose of this study was to examine how social media marketing, product quality, and location at Gerai Adila simultaneously and partially influence consumer purchasing decisions. A survey method was used to implement a quantitative approach; data from 387 respondents, collected through Google Forms, were selected using the Slovin formula from a population of 11,723 customers in 2024. In data analysis, instruments, classical assumptions, multiple linear regression, and hypothesis testing were conducted using SPSS 25. The results showed that social media marketing, product quality, and Gerai Adila's location partially had a positive and significant impact on consumer decisions to purchase products at Gerai Adila; social media marketing played a role in increasing consumer brand awareness and purchasing interest, while product quality influenced consumer satisfaction and trust. In addition, it was proven that all three variables had a positive and significant impact on purchasing decisions. The results show that to increase the competitiveness of souvenir shops in Jambi City, digital marketing strategies, consistent product quality, and the right location are important factors.